Executive Remuneration Policy at Banks in Poland After the Financial Crisis - Evolution or Revolution? - Słomka-Gołębiowska, Agnieszka; Urbanek, Piotr (Comparative Economic Research. Central and Eastern Europe, 2014)
The executive remuneration policy of financial institutions has been indicated as one of the key factors that led to the recent financial crisis. As a consequence a number of legislative initiatives and best practices have been imposed,aimed at strengthening existing and creating new standards of good corporate governance at banks. The purpose of this article is to assess the effectiveness of Poland’s new regulations concerning banks’ executive pay, which were introduced in the aftermath of the recent financial crisis. The research results indicate that the new legal rules have not been fully enforced. Public banks in Poland are not fulfilling the reporting obligations imposed by law and international principles. Given the crucial importance of executive remuneration policy in the financial sector to the stability of the banking sector, the inability to evaluate the progress made in the adjustment of executive remuneration practices to the new regulations may be perceived as one of the important risk factors that has not been effectively eliminated or even reduced in Poland yet.